Determination of Internal and External Factors of Sharia Banking In Turkey, Malaysia and Indonesia on The Business Risk And Profitability In 2013 – 2020 - Alamsurya Kubara Endriharto; Sri Hermuningsih; Gendro Wiyono (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
The purpose of this study is to compare the performance of Islamic banking in Turkey, Malaysia and Indonesia which consists of CAR, FAR, FDR, BOPO, Company Size, Inflation, Interest Rates, Exchange Rate, GDP, Asset Growth Rate, Business Risk, ROA. The sample in this study used purposive sampling and obtained a sample of 5 Islamic banks in Turkey, Malaysia, Indonesia. The data used is secondary data in the form of quarterly reports or financial reports through the official website of each Islamic bank. Researchers processed the data obtained based on purposive sampling using the annual reports of Islamic banking in Indonesia, Malaysia and Turkey in 2013-2020. The results show that BOPO on Business Risk is not significant in Turkey and Malaysia, but significant in Indonesia. CAR, FAR, and Exchange Rate against Business Risk are not significant in Turkey, Malaysia and Indonesia. FDR on Business Risk is not significant in Turkey and Indonesia, but significant in Malaysia. GDP, Interest Rate, Firm Size, Inflation, Asset Growth Rate to Business Risk are not significant in Malaysia and Indonesia, but significant in Turkey. BOPO to ROA is not significant in Turkey and Indonesia, but significant in Malaysia. CAR FAR Inflation Exchange Rate Asset Growth Interest rates on ROA are not significant in Turkey, Malaysia and Indonesia. GDP to ROA is not significant in Malaysia and Indonesia, but significant in Turkey. Firm size on ROA is not significant in Malaysia and Indonesia, but significant in Turkey. CAR FAR FDR to Asset Growth Rate is not significant in Turkey, Malaysia and Indonesia. Firm Size to Asset Growth Rate is not significant in Turkey, Malaysia and Indonesia. BOPO, Inflation, Exchange Rate, GDP to Asset Growth are not significant in Turkey and Malaysia, but significant in Indonesia.